Grace in Adversities: The Untold Stories of Dancesport Athletes with Disabilities - Balgos, Lionelle Rei (Community Development Journal, 2025)
Sports for persons with disabilities (PWDs) are increasingly gaining global recognition. However, their stories of struggle beyond the athletic arena remain underrepresented and insufficiently documented, particularly those of dancesports athletes with disabilities. This study explored and understood the narratives of dancesport athletes with disabilities. The researcher employed a qualitative research approach, specifically a narrative design. The participants were purposively chosen and interviewed through in-depth interviews using a validated interview guide. Cross-narrative analysis was employed to generate themes extracted from the participants' transcripts. The themes that emerged from the participants’ stories of struggles involved entering the sport with uncertainty and having a limited support system. The themes that reflected their accomplishments highlighted growth in confidence and the attainment of tangible milestones. Moreover, the themes identified from the coping mechanisms encompassed persistent skill practice, internal dialogue rooted in motivation, and reliance on an external support system. The participants also shared insights highlighting the need to strengthen inclusive sports programs and support networks to enhance the participation and visibility of persons with disabilities within the athletic community.